Long non-coding RNA APDC plays important regulatory roles in metabolism of bone and adipose tissues - Yao Liu; Zoe Xiaofang Zhu; Elissa K. Zboinski; Wei Qiu; Junxiang Lian; Shibo Liu; Thomas E. Van Dyke; Hans E. Johansson; Qisheng Tu; En Luo; Jake Jinkun Chen (RNA Biology)
The long noncoding RNA (lncR) ANRIL in the human genome is an established genetic risk factor for atherosclerosis, periodontitis, diabetes, and cancer. However, the regulatory role of lncR-ANRIL in bone and adipose tissue metabolism remains unclear. To elucidate the function of lncRNA ANRIL in a mouse model, we investigated its ortholog, AK148321 (referred to as lncR-APDC), located on chr4 of the mouse genome, which is hypothesized to have similar biological functions to ANRIL. We initially revealed that lncR-APDC in mouse bone marrow cells (BMSCs) and lncR-ANRIL in human osteoblasts (hFOBs) are both increased during early osteogenesis. Subsequently, we examined the osteogenesis, adipogenesis, osteoclastogenesis function with lncR-APDC deletion/overexpression cell models. In vivo, we compared the phenotypic differences in bone and adipose tissue between APDC-KO and wild-type mice. Our findings demonstrated that lncR-APDC deficiency impaired osteogenesis while promoting adipogenesis and osteoclastogenesis. Conversely, the overexpression of lncR-APDC stimulated osteogenesis, but impaired adipogenesis and osteoclastogenesis. Furthermore, KDM6B was downregulated with lncR-APDC deficiency and upregulated with overexpression. Through binding-site analysis, we identified miR-99a as a potential target of lncR-APDC. The results suggest that lncR-APDC exerts its osteogenic function via miR-99a/KDM6B/Hox pathways. Additionally, osteoclasto-osteogenic imbalance was mediated by lncR-APDC through MAPK/p38 and TLR4/MyD88 activation. These findings highlight the pivotal role of lncR-APDC as a key regulator in bone and fat tissue metabolism. It shows potential therapeutic for addressing imbalances in osteogenesis, adipogenesis, and osteoclastogenesis.